Microalgae-Based Ethanol Fermentation from Defatted Biomass: A Preliminary Study - Usman, Sukmawati; Agriandini, Maulina (Universitas Teuku Umar, 2025)
The utilization of microalgae has been widely carried out, ranging from food, feed, and cosmetics to alternative energy. Microalgae is a potential biomass source with lipid content ranging from 7% to 23% and carbohydrate content ranging from 4.6% to 23%. Microalgae can be utilized as a source of pigments and antioxidants. The ability of rapid cell growth is an advantage for microalgae. In addition, microalgae have lower lignin content compared to macroalgae. Tetraselmis chuii and Porphyridium cruentum are microalgae species that are known to contain lipids and carbohydrates that have the potential to be further utilized in the production of biodiesel and bioethanol. This study was conducted to determine the potential of microalgae biomass in bioethanol production through the fermentation process. This study was conducted to determine the potential of microalgae biomass in bioethanol production through the fermentation process. The pre-treatment stage consisted of a delipidation process with hydrolysis. The pretreated biomass was then fermented using Saccharomyces cerevisiae culture. Glucose and bioethanol levels were then observed every 24 hours. This study showed that the optimum time for bioethanol fermentation was 24 hours. Based on the analysis conducted using Tetraselmis chuii and Porphyridium cruentum biomass, the delipidation efficiency was 29.6362% and 40.2667%, and the hydrolysis efficiency was 8.49% and 7.51%. The bioethanol levels at the optimum fermentation time based on the refractive index test were 5.8% and 6.0%. The bioethanol levels based on gas chromatography analysis were 0.299% and 11.221%. This study shows that microalgae biomass has the potential as a substrate in bioethanol production and can be a reference for microalgae biomass-based bioethanol production on a larger scale.